(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the interrelationship between language and culture, emphasizing that language functions as a core carrier of cultural values, worldview, and collective memory. Drawing on global linguistic data and theoretical frameworks, the study highlights the urgency of preserving linguistic diversity, especially in multilingual societies such as Uzbekistan. Through analysis of sociolinguistic theories— including those of Fishman, Sapir–Whorf, Wierzbicka, Hall, and Hofstede—this work explores how communication styles, politeness norms, speech strategies, and humor patterns reflect deeper cultural structures. The article also analyzes Uzbek communicative behavior in contrast with Western low-context cultures, illustrating how cultural values shape linguistic choices. Findings underline the importance of understanding cultural-semantic systems for successful intercultural communication and language policy development.